Protocol for “Genetic composition of sickle cell disease in the Arab population: A systematic review” - Fateen Ata (12217764) (2023)
Background Sickle Cell Disease (SCD) is a global health issue in hematology with a progressively increasing prevalence. There are recent advances in the management of SCD, with new drugs being introduced. It is essential to analyze the genetic makeup of SCD regionally to anticipate the effectiveness of management modalities. This systematic review's main objectives are (a) to combine the existing knowledge of the genetic composition of SCD in the Arab population and (b) to analyze the various phenotypes of SCD prevalent in the Arab population. Methods We will perform a systematic review and search multiple electronic databases predefined search terms to identify eligible articles. Eligible studies should report findings on the genetic testing of Sickle Cell disease in the 22 Arab countries. Case reports, case series, observational studies with cross-sectional or prospective research design, case-control studies, and experimental studies will be included. Study quality will be independently evaluated by two reviewers using the statistical methodology and categories guided by the Cochrane Collaboration Handbook and PRISMA guidelines. Discussion This review will explore and integrate the evidence available on the various genotypes and phenotypes of SCD in the Arab population. By acquiring and summarizing data about the genetic and phenotypic variants of the SCD patient population, this study will add to the knowledge and help find more precise treatments. Systematic review registration The protocol is registered at the International Prospective Register of Systematic Reviews (PROSPERO; registration number: CRD42020218666). Other Information Published in: Health Science Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/hsr2.450